2022
DOI: 10.1159/000528553
|View full text |Cite
|
Sign up to set email alerts
|

Menthacarin, a Proprietary Peppermint Oil and Caraway Oil Combination, Improves Multiple Complaints in Patients with Functional Gastrointestinal Disorders: A Systematic Review and Meta-Analysis

Abstract: Introduction: This systematic review summarizes published data on Menthacarin, the proprietary combination of peppermint oil and caraway oil, in the treatment of functional gastrointestinal disorders. Efficacy was assessed by meta-analysis of placebo-controlled trials. Methods: We searched Pubmed, Cochrane library, and the manufacturer’s information system for clinical studies investigating the safety and efficacy of Menthacarin. Efficacy analyses included change from baseline of epigastric pain and general im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, more recently, the trial PERSUADE assessing small-intestinal release or ileocolonic release of peppermint oil showed that using the strict FDA and EMA endpoints, no significant reduction in overall symptom relief or abdominal pain was noted for both the preparations 96 . Recently, other formulations of essential oils were tested for IBS with promising results 97,98 . Otilonium bromide is a calcium channel blocker acting on the smooth muscle cells thus exerting a spasmolytic action.…”
Section: Abdominal Painmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recently, the trial PERSUADE assessing small-intestinal release or ileocolonic release of peppermint oil showed that using the strict FDA and EMA endpoints, no significant reduction in overall symptom relief or abdominal pain was noted for both the preparations 96 . Recently, other formulations of essential oils were tested for IBS with promising results 97,98 . Otilonium bromide is a calcium channel blocker acting on the smooth muscle cells thus exerting a spasmolytic action.…”
Section: Abdominal Painmentioning
confidence: 99%
“…96 Recently, other formulations of essential oils were tested for IBS with promising results. 97,98 Otilonium bromide is a calcium channel blocker acting on the smooth muscle cells thus exerting a spasmolytic action. In a pooled analysis, otilonium bromide was more effective than placebo in improving abdominal pain in patients with IBS with a significant therapeutic effect after 10 weeks of treatment and a maximal effect after 15 weeks.…”
Section: Abdominal Pain Antispasmodicsmentioning
confidence: 99%
“…Peppermint extract contains several bioactive components, including menthol, menthone, and rosmarinic acid. Menthol has potent anti-H. pylori activity [61]. The dosage of peppermint extract varies depending on the specific product and the condition being treated.…”
Section: Peppermintmentioning
confidence: 99%
“…Herbal remedies exert a broad spectrum of pharmacological actions (multi-target approach) combined with proven good tolerability [ 8 ] . Some herbal compounds exert prokinetic or anti-infl ammatory actions; volatile essential oils like peppermint oil [ 9 ] or caraway oil have strong carminative eff ects due to defoaming and spasmolytic activities [ 10 ] . Other herbal compounds seem to in-fl uence the microbiome by antibacterial and antifungal eff ects.…”
Section: Introductionmentioning
confidence: 99%